Psychological problems related to capillary blood glucose testing and insulin injection among diabetes patients - Pamungkas Rian Adi; Chamroonsawasdi Kanittha (Sciendo, 2020)
This review is aimed at explaining the psychological problems related to capillary blood glucose (CBG) testing and insulin injection, as well as recommending essential strategies to solve the fear thereof.